A COMPARATIVE STUDY OF MENTAL TOUGHNESS OF INTERUNIVERSITY AND NATIONAL LEVEL KABADDI PLAYERS OF MAHARASHTRA - Wankhede, Gowardhan Y; Kadwe, Mohan.D (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The aim of the present study is to study the Mental Toughness of interuniversity and national level kabaddip layers of Maharashtra. A total of 350 kabaddi players of Maharashtra have been selected as a sample of the study by purposive sampling method. In which 175 Inter University level and 175 National level Male Kabaddi players. Mental Toughness scale developed by Allan S. Goldberg has been used. To determine the psychological characteristics of different levels of Kabaddiplayers percentage and t-test has been calculated. Results indicate that most of the Inter University and National level Kabaddi players of Maharashtra have Moderate Mental Toughness. There is found no significant difference in Mental Toughness of inter university and national level kabaddi players of Maharashtra.